Direct and residual impacts of olive-mill waste application to rice soil on greenhouse gas emission and global warming potential under Mediterranean conditions - Fernández-Rodríguez, Damián (2022)
The olive oil industry produces high amounts of waste, which need to be valorized in a more sustainable way as an alternative to its traditional use as an energy source, with high associated CO2 emissions. Rice (Oryza sativa L.) is one of the most important crops for global food security; however, the traditional cropping systems under flooding lead to an important decrease of soil quality, as well as relevant emissions of greenhouse gases (GHG). The aim of this study was to assess the GHG emission from rice fields amended with composted two-phase olive mill waste (C-TPOW), in Mediterranean conditions. A field experiment was carried in rice cultivated by the traditional system, either unamended (Control) or amended with C-TPOW (Compost). GHG emissions were measured over three years following a single C-TPOW application (80 Mg ha−1 only in the first year of study), so that the results found in the first and third years correspond to its direct and residual effects, respectively. Compost decreased CO2 emissions relative to Control by 13% and 20% in the first and third year after C-TPOW application, respectively. However, in the case of CH4 and N2O, increases in the total cumulative emission were recorded in Compost relative to Control throughout the study, in agreement with the highest β-glucosidase and urease activity observed in the amended soil. The values of global warming potential (GWP) and yield-scaled GWP increased by 14% and 11%, respectively, in Compost relative to Control in the first year, but no significant differences between treatments were observed three years after application for GWP and yield-scaled GWP. Therefore, the use of C-TPOW as soil amendment in rice fields could be a good option since its impact on GHG